Influence of solidification conditions on TCP phase formation, casting porosity and high temperature mechanical properties in a Re-containing nickel-base superalloy with columnar grain structure - Volek, Andreas; Singer, Robert (Superalloys 2004: Proceedings of the 10th Intenational Symposium of Superalloys, 2004)
A coarse and a fine dendrite structure were produced using the newly developed DS-superalloy ExAl7 (≅ IN792 with 2-3 wt.-% Re) by changing the conditions of directional solidification. The two microstructures differed in their primary dendrite arm spacing by a factor of 1.6. During aging, very fine TCP phase precipitates (length approximately 20 μm, volume fraction ∼ 1%) were precipitated in the dendrite core, where the refractory element content was particularly high due to segregation. The finer dendrite structure resulted in a lesser tendency for TCP phase formation and smaller (but more numerous) casting pores. Creep strength was not affected by the dendrite size, apparently because TCP phase size and amount were still so small. Fatigue strength, however, was much improved by the finer dendrite structure. Casting pores were found to be somewhat larger than the TCP phases under the conditions investigated and to act as crack starters in fatigue.
Keywords: Creep; DS-superalloy; Fatigue; Porosity; Segregation; TCP phase formation